Plant-Mediated RNAi for Controlling Apolygus lucorum - Liu, Fangzhou; Yang, Bin; Zhang, Aihong; Ding, Derong; Wang, Guirong (Frontiers in Plant Science, 2019)
The polyphagous mirid bug Apolygus lucorum (Heteroptera: Miridae) is a serious pest of agricultural crops in China, with more than 200 species of host plants including two very important crops, maize and soybean. Currently, prevention and control of A. lucorum rely mainly on chemical pesticides that cause environmental as well as health related problems. Plant-mediated RNAi has proven to offer great potential for pest control in the past decade. In this study, we screened and obtained seven candidate genes (Alucβ-actin, AlucV-ATPase-A/D/E, AlucEif5A, AlucEcR-A, AlucIAP) by injection-based RNAi which produced A. lucorum mortality rates of 46.01% to 82.32% at day 7 after injection. Among them, the plant-mediated RNAi of AlucV-ATPase-E was successfully introduced into transgenic maize and soybean, and the populations of A. lucorum were significantly decreased following feeding on the transgenic maize and soybean. These results are intended to provide helpful insight into the generation of bug-resistant plants through a plant-mediated RNAi strategy. Key words: RNA interference, transgenic plants, non-bt, lethal gene, Apolygus lucorum